2012
DOI: 10.1007/s10886-012-0216-5
|View full text |Cite
|
Sign up to set email alerts
|

Semiochemicals from Herbivory Induced Cotton Plants Enhance the Foraging Behavior of the Cotton Boll Weevil, Anthonomus grandis

Abstract: The boll weevil, Anthonomus grandis, has been monitored through deployment of traps baited with aggregation pheromone components. However, field studies have shown that the number of insects caught in these traps is significantly reduced during cotton squaring, suggesting that volatiles produced by plants at this phenological stage may be involved in attraction. Here, we evaluated the chemical profile of volatile organic compounds (VOCs) emitted by undamaged or damaged cotton plants at different phenological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 39 publications
5
70
1
1
Order By: Relevance
“…aphids, leafhoppers, stinkbugs (Hegde et al 2011; Moraes et al 2009; Oluwafemi et al 2011; Sobhy et al 2017), and in indirect defence via recruitment of natural enemy parasitic wasps (Bruce et al 2008; Li et al 2017; Moraes et al 2009; Tamiru et al 2011). Furthermore, Magalhães et al (2012) suggested that cotton boll weevils, Anthonomus grandis recognize the physiological stage of host cotton plants via information on the amount of DMNT and TMTT released by cotton plants. Male and female A. grandis prefer plants that produce lower amounts of DMNT and TMTT, allowing discrimination between plants at the reproductive and vegetative stages (Magalhães et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…aphids, leafhoppers, stinkbugs (Hegde et al 2011; Moraes et al 2009; Oluwafemi et al 2011; Sobhy et al 2017), and in indirect defence via recruitment of natural enemy parasitic wasps (Bruce et al 2008; Li et al 2017; Moraes et al 2009; Tamiru et al 2011). Furthermore, Magalhães et al (2012) suggested that cotton boll weevils, Anthonomus grandis recognize the physiological stage of host cotton plants via information on the amount of DMNT and TMTT released by cotton plants. Male and female A. grandis prefer plants that produce lower amounts of DMNT and TMTT, allowing discrimination between plants at the reproductive and vegetative stages (Magalhães et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Showler (2002) demonstrated that the boll weevil is less inclined to use kaolin-coated cotton plants for feeding and oviposition, indicating that visual stimuli are important for the recognition of cotton plants by cotton boll weevil. However, a study that characterized boll weevil responses to the volatiles released by cotton in different growth stages and herbivorous conditions in olfactometer, showed that A. grandis uses conspecific herbivore-induced volatiles enriched with the aggregation pheromone to locate host cotton plants and that terpenic compounds may be involved in their attractiveness (Magalhães et al, 2012). This result suggests that the olfactory stimulus is also important probably at short distance.…”
Section: Discussionmentioning
confidence: 99%
“…Here we also report that F. occidentalis showed very different responses to damage by H. armigera or T. urticae; it preferred undamaged plants to those damaged by H. armigera, but preferred plants damaged by T. urticae over undamaged plants. types of feeding damage (i.e., chewing vs. sucking) inflicted (Magalhães et al, 2012). This suggests that the attractiveness of the HIPVs induced by T. urticae damage was able to overcome the "repellency" of the HIPVs induced by H. armigera damage but only for 2 d (compared with 4 d of attraction to T. urticae damage alone).…”
Section: Figmentioning
confidence: 99%